The Combination Effects of Resveratrol and Swimming HIIT Exercise on Novel Object Recognition and Open-field Tasks in Aged Rats. Issue 4 (7th August 2020) - Amirazodi, Fatemeh; Mehrabi, Amin; Amirazodi, Maryam; Parsania, Shahrnaz; Rajizadeh, Mohammad Amin; Esmaeilpour, Khadijeh
ABSTRACT: Introduction: Resveratrol, a natural polyphenol abundant in grapes and red wine, has been reported to exert numerous beneﬁcial health effects in the body. High-Intensity Interval Exercise (HIIT) is a form of interval training that provides improved athletic capacity and has a protective effect on health. The purpose of this study was to investigate the interactive effects of swimming HIIT and Resveratrol supplementation on behavioral function in Novel object recognition and open-field tests in aged rats. Methods: A total of 45 aged male Wistar rats with an age of 20 months were randomly assigned into five groups of control (C), swimming HIIT (SW-HIIT), swimming HIIT with Resveratrol supplementation (SW-HIIT-R), Resveratrol supplementation (R), and solvent of Resveratrol supplementation (SR). There was also another group that included young animals (2-month-old) and was used to compare with older animals. Swimming HIIT and Resveratrol supplementation groups performed the exercise and received Resveratrol (10 mg/kg/day, gavage) for six weeks. Novel object recognition and open-field tests were used for evaluating the behavioral functions in animals. Results: The results showed that HIIT and Resveratrol significantly improved recognition memory compared to old animals. Moreover, it seems that HIIT and Resveratrol partly could modulate anxiety-like behaviors compared to old animals in the open-field test.